2019
DOI: 10.28991/cej-2019-03091274
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Expansive Soils Using Polypropylene Fiber

Abstract: Current research main aim is to study the effect of adding polypropylene fiber (PPF) on the behavior of expansive soil to reduce the swelling as percentage (0.5, 1 and 2%) of the weight of dry soil. Expansive soil used in this research was prepared artificially by mixing Ca-based bentonite from geological survey and mining company with sandy soil brought from Karbala city as percentage 80% bentonite to 20% sand of dry weight. Multiple laboratory tests have been carried are (Unconfined Compression Test, One-Dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…[30] evaluated the environmental sustainability performance of microbentonite. [31] did research on the role of polypropylene fibers in expansive soils, and [32] looked at how magnesium bentonite alkalizes at the microscopic level in alluvial sand. [33] evaluated the role of NaCl as a case study in alluvial soils.…”
Section: The Use Of Bentonite Strengthens the Soilmentioning
confidence: 99%
“…[30] evaluated the environmental sustainability performance of microbentonite. [31] did research on the role of polypropylene fibers in expansive soils, and [32] looked at how magnesium bentonite alkalizes at the microscopic level in alluvial sand. [33] evaluated the role of NaCl as a case study in alluvial soils.…”
Section: The Use Of Bentonite Strengthens the Soilmentioning
confidence: 99%
“…The experimental results showed that the mechanical characteristics was improved with the addition of polypropylene fibers. Hussein and Ali (2019) studied the effect of adding polypropylene fiber on the behavior of expansive soil. In this study Unconfined Compression Test, One-Dimensional Consolidation Test, Swelling Test, Sieve Analysis and Cycle Swell Shrink Test were carried out and test results were saved.…”
Section: General Properties Of Polypropylene Fibersmentioning
confidence: 99%
“…and (2) chemical stabilization (by adding materials such as fly ash, salts, cement, lime, etc.). Recently, the addition of synthetic fibers [5][6][7][8][9][10][11][12][13] and natural fibers [13][14][15][16][17][18][19] has been considered among effective soil improvement techniques. Many studies have shown that the use of fibers (of natural or synthetic origin) gives satisfying results regarding the expansive behavior of soils [1-4, 8, 9, 12-14].…”
Section: Introductionmentioning
confidence: 99%
“…After two years, Pekrioglu (2017) studied the mechanical properties of a mixture of polypropylene fiber and marble dust on gypsum-stabilized soil [23]. Hussein and Ali (2019) discussed the effect of polypropylene fibers on expansive soil [8]. Tomar et al (2020) studied a mixture of polypropylene fiber and nanosilica regarding its durability and strength [11].…”
Section: Introductionmentioning
confidence: 99%